Critical Knowledge, Points of Confusion, and Training Recommendations for Client Referrals - Jessica Lloyd-Hazlett; Samantha Airhart-Larraga; Lucy L Purgason (Teaching and Supervision in Counseling, 2020)
The intersection of personal and professional values in relation to client referrals may cause uncertainty and confusion among counseling students. Current literature on this topic demonstrates a lack of agreement exists among student counselors about how to navigate the referral process, especially as it relates to making decisions about when to refer (Author, 2017). This content analysis examines what student counselors (N=104) perceive as critical areas of knowledge, points of confusion, and suggestions for training on ethical referrals. Emergent themes and implications for counselor education and future research are discussed.
Keywords: client referrals; counselor education; ethics